Real-Life Experience With Subcutaneous Plasma-Derived C1-Inhibitor for Long-Term Prophylaxis in Patients With Hereditary Angioedema: A Case Series - Zanichelli, Andrea; Suffritti, Chiara; Popescu Janu, Valentina; Merlo, Andrea; Cogliati, Chiara (Frontiers in Allergy, 2022)
Hereditary angioedema due to C1-inhibitor deficiency (C1-INH-HAE) is characterized by swelling attacks that may be even life-threatening. To reduce the frequency of attacks, some patients need a long-term prophylaxis (LTP). In addition to the intravenous administration, plasma-derived C1-inhibitor (pdC1-INH) proved effective also if administered subcutaneously at the dose of 120 IU/kg/week. In this case series, we collected from clinical records data about 5 patients with poorly controlled C1-INH-HAE with the registered LTPs or with difficult venous access, referred to the angioedema center in Milano (Italy), who received it at lower doses, i.e., 42.86-65.22 IU/kg/week. All the patients experienced a reduction in attack rate, ranging from 29.67% to 96.53% comparing with a control period with a different LTP of with no LTP. For one patient the comparison was made with a period when he received s.c. pdC1-INH 2 (with poor outcomes) instead of 3 times a week, that made the patient experience a decrease in attack rate from 5.26 to 1.12 attacks/month. Observation periods varied between 2.6 and 47.97 months. Two patients reported adverse events, that were localized at the infusion site and mild in severity. In conclusion, subcutaneous pdC1-INH represents an alternative therapeutic choice according to the physician’s judgment for selected HAE patients poorly controlled with registered LTPs. In patients with difficult venous access, in countries where pdC1-INH is not approved for subcutaneous administration, about half the recommended dose may be beneficial, though suboptimal results may be obtained.